2017
DOI: 10.1002/jwmg.21267
|View full text |Cite
|
Sign up to set email alerts
|

Nest site selection and nest survival of eastern wild turkeys in a pyric landscape

Abstract: Pine (Pinus spp.)‐dominated forests are commonly managed with prescribed fire in the southeastern United States to reduce fuel loads, maintain diverse plant communities, and increase habitat quality for wildlife. Prescribed fire alters understory vegetation, which is a key component of nesting habitat for ground‐nesting birds. We assessed the influences of vegetation, prescribed fire, and landscape features (e.g., roads, edge) on nest site selection and nest survival of eastern wild turkeys (Meleagris gallopav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
138
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 57 publications
(141 citation statements)
references
References 40 publications
2
138
1
Order By: Relevance
“…We found that females selected nest sites with increased visual obstruction but daytime use sites with decreased visual obstruction. Conversely, visual obstruction was not an important predictor of nest site selection in a fire‐managed landscape in Louisiana, USA (Yeldell et al ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that females selected nest sites with increased visual obstruction but daytime use sites with decreased visual obstruction. Conversely, visual obstruction was not an important predictor of nest site selection in a fire‐managed landscape in Louisiana, USA (Yeldell et al ).…”
Section: Discussionmentioning
confidence: 99%
“…We did this to create a more conservative estimate of space use because a new UD would be overly biased towards locations taken during the incubation period (Cohen et al ). To facilitate comparisons with recent studies, we mirrored the methodology of Yeldell et al (), and generated 5 paired random locations within each pre‐nesting range for each individual female across each nest attempt. To calculate landscape characteristics at ground roosts and daytime use sites, we constructed daily ranges using 100% minimum convex polygons around GPS locations for the day prior to roost sampling, and around GPS locations for the day of daytime use sampling.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations